PENGUATAN EKONOMI KELUARGA NELAYAN MELALUI RAGAM PENGOLAHAN HASIL PERIKANAN PASCA PENANGKAPAN IKAN DI DESA BARANGKALANG KECAMATAN MANGANITU KABUPATEN KEPULAUAN SANGIHE - Andaki, Jardie A. (Universitas Sam Ratulangi, 2015)
Abstract The purpose of this study to determine the model of economic strengthening of fisher families through a variety of fish processing post-arrest. This study design case study, which researchers are trying to describe and give explanations about the model of economic strengthening families through a variety of post-processing of fishermen fishing. Qualitative methods used in this study, the research aims to understand the phenomenon of what is experienced by the subject of the study such behavior, perception, motivation, action and others, holistically and by way of description in the form of words and language, in a special natural context and with using various scientific methods (Moleong, 2009). Sources of data in the form of primary data obtained from informants who were subjected to the study. Informants are certain individuals who gave a detailed interview for information purposes in getting data. Acquisition of data sourced directly from the field into the observation. Secondary data were obtained from sources of relevant literature such as books, journals, magazines, and the internet. Data collection techniques and data recording is done by direct observation, interviews and documentation. Learning simple accounting, including financial analysis simple, able to open up the minds of the group in determining the accuracy of financial and business development potential for the processing of fishery products. Through counseling and discussion, both groups